Erosion Resistant Hydrophobic Coatings for Passive Ice Protection of Aircraft - Naiheng Song; Ali Benmeddour (Applied Sciences, 2022)
Novel polymeric coatings, namely slippery polyurethane (SPU) coatings, with high surface hydrophobicity and superior erosion resistance against high speed solid particles and water droplets were successfully developed to protect the leading edge of fast moving aerodynamic structures, such as aircraft wings and rotor blades, against ice accretion. The coatings comprise newly synthesized surface-modifying polymers (SMPs) bearing fluorinated and polydimethylsiloxane branches at a loading level of 1–5 wt.%, based on the total resin solid, which showed good compatibility with the erosion-resistant polyurethane matrix (PU-R) and rendered effective surface hydrophobicity and slipperiness to the coatings, as evidenced by the high water contact angles of 100–115°. The coatings can be easily be sprayed or solution cast and cured at ambient temperature to provide highly durable thin coating films. X-ray photoelectron spectroscopy (XPS) investigation showed concentration of fluorine on the surface. The presence of 1–5 wt.% of SMPs in the polyurethane matrix slightly reduced the tensile modulus but had no significant impact on the tensile strength. All coating films exhibited good thermal stability with no material softening or degradation after heating at 121 °C for 24 h. DSC heating scans revealed no thermal transitions in the temperature range of −80 °C to 200 °C. Ice adhesion strength (IAS) tests using a static push rig in a cold room of −14 °C showed IAS as low as 220 kPa for the SPU coatings, which is much lower than that of PU-R (i.e., about 620 kPa). Sand erosion tests using 50 μm angular alumina particles at an impinging speed of 150 m/s and an impinging angle of 30° revealed very low erosion rates of ca. 100 μg/g sand for the coatings. Water droplet erosion tests at 175 m/s using 463 μm droplets with 42,000 impingements every minute showed no significant coating removal after 20 min of testing. The combination of the high surface hydrophobicity, low ice adhesion strength and superior erosion resistance makes the SPU coatings attractive for ice protection of aircraft structures, where the coatings’ erosion durability is of paramount importance.